THE RELIGIOUS GUIDANCE FOR PROSTITUTE A Descriptive Study at Palimanan Cirebon - Murip Yahya (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
This study attempts to investigate the implementation of religious guidance for prostitute and its influence to Woman Social Institution Silih Asih in Palimanan, Cirebon. It formulated on four research questions: 1) How is the process of religious guidance in Social Institution Silih Asih; 2) What is the participants’s efforts to achieve the goal of religious guidance; 3) How is the material of religious guidance in Social Institution Silih Asih Palimanan; 4) How is the approach and method of religious guidance applied in Social Institution Silih Asih Palimanan to support and achieve the aim of religious guidance. The study used qualitative-naturalistic, research design with descriptive method. The data were collected through observation, interview, and document analysis. The results of the study show that: 1) there were two stages of religious guidance: identification stage and rehabilitation process; 2) the participants were identified by their age, marital status, education background, parents’ job, and reasons of being prostitute; 3) the materials presented on theoretical and natural materials based on Islam thoughts; 4) the religious guidance used various approaches: experience, habituation, emotional, rational, and holistic.